2018
DOI: 10.5194/esurf-6-1059-2018
|View full text |Cite
|
Sign up to set email alerts
|

Towards a standard typology of endogenous landslide seismic sources

Abstract: Abstract. The objective of this work is to propose a standard classification of seismic signals generated by gravitational processes and detected at close distances (<1 km). We review the studies where seismic instruments have been installed on unstable slopes and discuss the choice of the seismic instruments and the network geometries. Seismic observations acquired at 13 unstable slopes are analyzed in order to construct the proposed typology. The selected slopes are affected by various landslide types (sl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 151 publications
(226 reference statements)
3
56
0
Order By: Relevance
“…DEM = digital elevation model. signals described in previous studies (Helmstetter & Garambois, 2010;Provost et al, 2018). The configuration of the network, with large distances between stations, does not allow us to use the apparent velocity or the intertrace correlation as classifying parameters.…”
Section: Detection and Classification Of Seismic Signalsmentioning
confidence: 96%
“…DEM = digital elevation model. signals described in previous studies (Helmstetter & Garambois, 2010;Provost et al, 2018). The configuration of the network, with large distances between stations, does not allow us to use the apparent velocity or the intertrace correlation as classifying parameters.…”
Section: Detection and Classification Of Seismic Signalsmentioning
confidence: 96%
“…After the seismic signals of both landslide events were received at the nearest monitoring station (MID; 10 km), the seismic wave reached the DUG station (68 km) in approximately 30 s. The study used the Hilbert-Huang transform (HHT) method to analyze the seismic signals received by the DUG monitoring station, and the results revealed that the energy peaked 1 min after receiving the signals and was concentrated at 5 Hz. Provost et al [19] proposed a classification of seismic signals generated by various types of landslide processes, including slide, fall, topple, and flow. They analyzed duration, frequency content, and spectrogram shape of the seismic sources acquired from 13 unstable slopes and categorized the signals into three main classes-"slope quake", "rockfall", and "granular flow"-based on the characteristics of the signals.…”
Section: Introductionmentioning
confidence: 99%
“…5c.). The second type of endogenous signals is generated by slopequakes; these sources are assumed to result from stress release by both fracture opening or shearing (Helmstetter & Garambois 2010;Walter et al 2013;Tonnellier et al 2013;Vouillamoz et al 2017;Provost et al 2018). The recorded signals last less than 5 s and different waveforms and frequency content may be observed (Provost et al 2018).…”
Section: Microseismic Monitoring and Seismic Signal Descriptionmentioning
confidence: 99%
“…The second type of endogenous signals is generated by slopequakes; these sources are assumed to result from stress release by both fracture opening or shearing (Helmstetter & Garambois 2010;Walter et al 2013;Tonnellier et al 2013;Vouillamoz et al 2017;Provost et al 2018). The recorded signals last less than 5 s and different waveforms and frequency content may be observed (Provost et al 2018). It must be noted that some events are only recorded by one of the seismic arrays (Walter et al 2012;Tonnellier et al 2013;Vouillamoz et al 2017) and that the intertrace correlation of the whole signal is low due to scattering and dispersion of the seismic waves (Walter et al 2012;Tonnellier et al 2013).…”
Section: Microseismic Monitoring and Seismic Signal Descriptionmentioning
confidence: 99%
See 1 more Smart Citation